APPLICATION OF AN IMPROVED WORKING BODY IN THE REBURIAL OF CLOSED HORIZONTAL DRAINAGE TRENCHES (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
The article describes the work to be done to improve land reclamation. Problems encountered in soil compaction and reburial of excavated trenches, as well as the scheme of an improved toothed roller for compacting the soil of newly opened trenches, are shown, and suggestions are made to prevent excessive costs.